The scale insect Dynaspidiotus abietis (Schrank) on Abies cephalonica (Pinaceae) - Stathas, G. J. (ENTOMOLOGIA HELLENICA, 2008)
Data on phenology and morphology of the scale insect Dynaspidiotus abietis (Schrank) (Hemiptera: Diaspididae), found on fir trees Abies cephalonica (Pinaceae) on mount Taygetos (Peloponnesus - southern Greece), are presented. The species is biparental and oviparous. During this study (June 2004 – August 2006) D. abietis completed one generation per year. It overwintered as mated pre-ovipositing female adult. Ovipositions were recorded from May to July. The majority of the hatches of the crawlers were observed in June. Predated individuals of the scale which were found during the study period were attributed to the presence of the predator Chilocorus bipustulatus (L.) (Coleoptera: Coccinellidae).